Teacher Readiness in Teaching English for Young Learners among Indonesian Preservice Primary Teachers - Murti Ayu Wijayanti; Kintan Nurwinanda; Abdul Fatah (Journal of English Language Studies, 2025)
Teaching English for Young Learners (TEYL), especially in the context of Indonesia, requires specific capacities of the teachers to manage the students and the learning process. However, challenges may appear due to the complexity of teaching English to young learners. It renders a question whether pre-service teachers have readiness to handle TEYL.   This study involved 125 preservice primary school teachers joining Preservice Teacher Professional Education (PPG bagi Calon Guru) in a public university in Banten Province, Indonesia. This qualitative research employed questionnaire and interview techniques to gather the data. The data of preservice primary teachers’ readiness towards this policy were collected. In addition, the challenges and the participants’ expectations were examined. The results of the research indicate that most of the respondents do not know that English will be mandatory subject in primary school next year and classroom teachers will be required to teach this subject. The result of the study shows that that once they enter the teaching realm, most of them are ready to teach. To get prepared, they learn English and how to teach English for young learners. In terms of the biggest challenges that they might encounter are limited vocabulary and materials and speaking ability. They expected to get English for primary school subject as well as English training. To conclude, the university conducting Preservice Teacher Professional Education (PPG bagi Calon Guru) as well as the government should provide help for the students to set their readiness to teach English.